Pengaplikasian Inovasi Ecobrick Solusi Berkelanjutan dalam Pengelolaan Limbah Botol Plastik pada Siswa SDN 026 Rambah Samo Kabupaten Rokan Hulu - Adrina Takifa; Arya Desmitra Wicaksono; Fauzan Kamil; Intan Nuraini; Jetro Valinus Sembiring; Muhammad Haekal; Mun Holidah; Muthia Safitri Ritonga; Nadia Syahraini; Nur Hasnah AR; Riswanda Riyani Basuki (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of plastic waste and used bottles in Lubuk Napal Village was innovated into Ecobricks which were implemented at SDN 026 Rambah Samo. The aim of this activity is to foster sensitivity, awareness, concern and creativity to use and process waste as best as possible. This activity produces benches and tables that can be used by students in the reading garden at SDN 026 Rambah Samo.